Bosniak IIF and III Renal Cysts: Can Apparent Diffusion Coefficient–Derived Texture Features Discriminate Between Malignant and Benign IIF and III Cysts?. Issue 3 (May 2019) - Gillingham, Nicolas; Chandarana, Hersh; Kamath, Amita; Shaish, Hiram; Hindman, Nicole
Abstract : Objective: The aim of this study was to determine which apparent diffusion coefficient–derived texture features are associated with malignancy in Bosniak IIF and III renal cystic lesions. Methods: Twenty benign and 7 malignant Bosniak IIF (22) or III (5) renal cysts, as evaluated with magnetic resonance imaging, were assessed for progression to pathology-confirmed malignancy. Whole-cyst volumes of interest were manually segmented from apparent diffusion coefficient maps. Texture features were extracted from each volume of interest, including first-order histogram-based features and higher-order features, and data were analyzed with the Mann-Whitney U test to predict malignant progression. Results: Eleven of 17 first-order features were significantly greater in benign compared with malignant cysts. Eight higher-order gray-level co-occurrence matrix (GLCM) texture features were significantly different between groups, 5 of which were greater in the benign population. Conclusions: Apparent diffusion coefficient–derived texture measures may help differentiate between benign and malignant Bosniak IIF and III cysts.